Investigation of Modifying Alloying Elements in High-Pressure Injection Casting Eutectic Al-Si Alloys - Alpaslan Kılıçarslan; Hatem Akbulut (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2024)
In the study, the mechanical properties of aluminum alloys produced by the injection molding method, especially using Strontium and Titanium metals, were optimized without being subjected to cold forming. Mechanical tests were applied to the alloys produced by the high-pressure casting technique, and their strength, hardness, and microstructure were examined. Optical and SEM microscopy examinations investigated grain structures. Within the scope of the study, AlTi5B1 master alloy and AlSr10 master alloy were added to the pure AlSi10 (Fe) alloy in 5 different compositions. AlTi5B1 master alloy added to pure AlSi10(Fe) alloy significantly increased the hardness by reducing the grain size. Si modification took place with the addition of AlSr10 master alloy, and it was observed that the obtained weight ratios of 150ppm, 300ppm, and 450ppm Sr increased the hardness proportionally by 2.5 HB each. With the increase in Ti and Sr master alloys added, a significant increase was observed in tensile and yield strengths and % elongation rates. In the compression test, the percentage (%) deformation elongation, the reduction of the grain structure of the material by the added Ti and Sr elements, and the transformation of the eutectic silicon into a spherical structure absorbed the applied Fm force. This led to an increase in strength, and while the permanent deformation elongation decreased as the weight of Ti increased, it was observed that the permanent deformation elongation decreased proportionally with each added amount of 150 ppm Sr. The addition of the Ti element reduced the grain size by shrinking the α-Al dendrites, but it did not affect the eutectic Si.